2022
DOI: 10.1088/1742-6596/2217/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Experimental transient cavitation bubbles in a conical-frustum shaped tube

Abstract: Extreme flow acceleration in the water can induce large cavitation bubbles in the hydraulic machinery, and cause liquid column separations in the pipeline. The abrupt collapse of these large bubbles produces strong pressure oscillation and causes catastrophic destruction instantaneously. Considering the complexity of the shapes of pipelines in engineering, we experimentally study the transient bubble dynamics in a conical-frustum shaped tube by a modified tube-arrest method in the present paper. Three shapes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results showed that the jet velocity of the bubbles is influenced by the liquid inertia on the bubble surface and is related to the bubble position and the inner diameter of the tube section. Wang et al, (2022) [35] considering the complex shape of tubes in engineering, the modified tube - arrest method was employed to investigate the transient cavitation bubble in a conical - frustum - shaped tube. Three morphologies of cavitation bubble generation were observed, and it was pointed out that the location and morphology of cavitation bubble strongly depended on the tube sizes and roughness of tube wall.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the jet velocity of the bubbles is influenced by the liquid inertia on the bubble surface and is related to the bubble position and the inner diameter of the tube section. Wang et al, (2022) [35] considering the complex shape of tubes in engineering, the modified tube - arrest method was employed to investigate the transient cavitation bubble in a conical - frustum - shaped tube. Three morphologies of cavitation bubble generation were observed, and it was pointed out that the location and morphology of cavitation bubble strongly depended on the tube sizes and roughness of tube wall.…”
Section: Introductionmentioning
confidence: 99%